EVEKTIVITAS PEMBELAJARAN KEWARGANEGARAAN MELALUI VARIASI MODEL PEMBELAJARAN MODULER DENGAN MODEL PEMBELAJARAN MEANING FULL LEARNING - M. JUFRI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The purpose of the study was to determine the extent to which student activities in civics learning apply variations of the modular learning model with the Meaning full learning learning model in class XII IPS 3 SMA Negeri 3 Takalar and to determine the effectiveness of civics learning through variations of the modular learning model with the Meaning full Learning learning model. in class X SMA Negeri 3 Takalar. The results showed that: (1) the application of the modular learning model and Meaning full learning in various variations in Civics learning can increase student learning activities which include interest in working on modules, creativity in working on modules, independence in working on modules, completing modules on time, quality of module results, interest in following the discussion, submitting opinions/responses, noting important things about the discussion, obeying the discussion rules, and the quality of the discussion results, (2) the application of the modular learning model and the Meaning full learning learning model in various ways can make Civics learning effective. This can be seen from the observational data on student activities which increased from 69.92% in the first cycle to 81.58% in the second cycle and the average value of the students' cognitive assessment results which also increased and reached the KKM, namely from 70.07 in the first cycle to 84.33 in the second cycle, and (3) the role of the teacher in the teaching and learning process that applies the modular learning model and the MFL learning model is very important as a supporter of increasing student learning activities and improving learning achievement. ABSTRAKTujuan penelitian adalah untuk mengetahui sejauh mana aktivitas siswa dalam pembelajaran Kewarganegaraan yang menerapkan variasi model pembelajaran moduler dengan model pembelajaran Meaning full learning pada kelas XII IPS 3 SMA Negeri 3 Takalar dan untuk mengetahui efektivitas pembelajaran Kewarganegaraan melalui variasi model pembelajaran moduler dengan model pembelajaran Meaning full Learning pada siswa kelas X SMA Negeri 3 Takalar. Hasil penelitian menunjukkan bahwa: (1) penerapan model pembelajaran moduler dan Meaning full learning secara bervariasi dalam pembelajaran Kewarganegaraan dapat meningkatkan aktivitas belajar siswa yang meliputi minat mengerjakan modul, kreativitas mengerjakan modul, kemandirian mengerjakan modul, menyelesaikan modul tepat waktu, mutu hasil modul, minat mengikuti diskusi mengajukan pendapat/ tanggapan, mencatat hal penting tentang diskusi, mentaati aturan diskusi, dan mutu hasil diskusi, (2) penerapan model pembelajaran moduler dan model pembelajaran Meaning full learning secara bervariasi dapat mengefektifkan pembelajaran Kewarganegaraan. Hal ini dapat dilihat data hasil observasi terhadap aktivitas siswa yang meningkat dari 69,92 % pada siklus I menjadi 81,58 % pada siklus II dan nilai rata-rata hasil penilaian kognitif siswa yang juga meningkat dan mencapai KKM, yaitu dari 70,07 pada siklus I menjadi 84,33 pada siklus II, dan (3) peranan guru dalam proses belajar mengajar yang menerapkan model pembelajaran moduler dan model pembelajaran MFL sangat penting sebagai pendukung peningkatan aktivitas belajar siswa dan peningkatan prestasi belajar.